The genus Lithophyllum in the north-western Indian Ocean, with description of L. yemenense sp. nov., L. socotraense sp. nov., L. subplicatum comb. et stat. nov., and the resumed L. affine, L. kaiseri, and L. subreduncum (Rhodophyta, Corallinales) - Basso, Daniela; Caragnano, Annalisa; Le Gal, Line; Rodondi, Graziella (Phytotaxa, 2015)
Based on literature, the genus Lithophyllum was represented in the whole Indian Ocean by 14 taxa, mostly in need of revision in a modern context. Molecular analyses integrated with morpho-anatomical comparisons between the recently revised type material of Lithophyllum kotschyanum Unger, and the related infraspecific taxa, lead to a resumption of L. affine, L. kaiseri, and L. subreduncum, and the description of L. socotraense sp. nov., L. yemenense sp. nov., and L. subplicatum comb. et stat. nov. Detailed accounts are provided for each species, including keys, along with information on synonymy, examined collections, distribution, habitat as well as sequence data of the 5’ end of the LSU from the type specimens. The anatomical features of the tetrasporangial conceptacle that were considered collectively diagnostic for species identification are: the mean diameter of the tetrasporangial conceptacles, the length of the pore-canal in the tetrasporangial conceptacles (with the number of cells in roof filaments), the occurrence of a depression at the top of the conceptacle roof in relation to the pore opening, and the number of cells from the floor of the tetrasporangial conceptacle chamber to the thallus surface. This study provides evidence of a previously unsuspected diversity within the Red Sea and NW Indian Ocean species of Lithophyllum.